Impact of Leadership Styles on Conflict Management in Federal Universities South-South, Nigeria - Omwanghe, Etinosa James; Omoregie, Godsent Osagie (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025DO - 10.58709/niujhu.v10i1.2105, 2025)
This study investigated the impact of leadership styles on conflict management among librarians in federal universities in South-South, Nigeria. The research adopted a quantitative approach using survey design, with a population of 85 academic librarians from university libraries in the region. Data was collected through structured questionnaires and analyzed using descriptive and inferential statistics. The study revealed that employees predominantly utilize collaborative approaches in conflict management (grand mean = 3.30), followed by avoidance (3.23), accommodating (3.15), sharing (2.97), and dominating strategies (2.61), with over 90% of respondents actively listening for solutions.The study examined two primary leadership styles – transformational and transactional – and their impact on conflict management effectiveness. The findings revealed a strong positive correlation between leadership styles and conflict management (r = .724, p < .05), with leadership styles explaining 52.4% of the variance in conflict management effectiveness. Transformational leadership emerged as the dominant style (β = .524), characterized by high scores in approachability (M = 3.36) and team work facilitation (M = 3.27). While transactional leadership showed a lower but significant influence (β = .369). The study concluded that both leadership styles significantly influence conflict management, with transformational leadership having a stronger impact. Recommendations include investment in leadership development programs and establishment of formal mentoring systems to enhance conflict management capabilities in university libraries. Keywords: Leadership styles, conflict Management, University libraries, Library personnel.